Volume 3A: Coal, Biomass and Alternative Fuels; Cycle Innovations; Electric Power; Industrial and Cogeneration 2014
DOI: 10.1115/gt2014-25438
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Environmental Load Reduction in Heavy Duty Gas Turbine by Bleeding Lines

Abstract: The power generation and energy market scenarios are requiring the power generation plants to fulfill more flexible operations respect to the recent past. One of the main concerns of plant operators is the lowering of minimum load at which the machines can be exercised while respecting the pollution limits. A strategy to improve minimum turndown capability by reducing the minimum environmental load of heavy duty axial gas turbines is here presented: it is based on the use of the compressor air bleeding lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In all the presented simulations, mixing planes with non-reflecting boundary conditions (Giles [8,9]) have been adopted to couple consecutive rows. A local matching interface was used between the last stator and the OGV since they share the same blade count [4,3].…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the presented simulations, mixing planes with non-reflecting boundary conditions (Giles [8,9]) have been adopted to couple consecutive rows. A local matching interface was used between the last stator and the OGV since they share the same blade count [4,3].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Despite their rapid development expected over the next decades, gas-fired power plants are required to maintain a key role in the energy horizon, in order to ensure grid stability and peak demand, and so to reach extreme off-design conditions. The increasingly restrictive regulations imposed by the European community have led to strong interest in the development and optimization of technologies, that can be retrofitted to an existing combined-cycle power plant to enhance flexibility, as well as increase performance and lower emissions (General Electric [12], Alstom Power [18], Ansaldo Energia [3]).…”
Section: Introductionmentioning
confidence: 99%
“…The increasingly restrictive regulations imposed by the European community have led to strong interest in the development and optimization of technologies that can be retrofitted to an existing combined-cycle power plant to enhance flexibility as well as increase performance and lower emissions (General Electric [4], Alstom Power [5], Ansaldo Energia [6]).…”
Section: Introductionmentioning
confidence: 99%
“…For GTs, it is desirable to reduce the low load capability without exceeding the CO limits. This can be made possible by some approaches that include Variable Inlet Guide Vane (VIGV) extension [4], use of bleed-off valves (BOV) [5] and through bleed extraction for storage (Compressed Air Energy Storage -CAES) that applies to this study. Pratyush et al [6] in a Siemens study indicated that extended VIGV closure, bypassing compressed air around the combustor, and optimizing rotor cooling can bring about a MEL of 40% and 28% (without and with catalytic CO capturing respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Alstom explored the use of sequential burners in their GT26, currently owned by Ansaldo Energia; Ruchti et al [7] suggest that the engine could achieve a MEL of 20% by switching off one of its burners and still operate satisfactorily in combined cycle operation. More recently, Ansaldo Energia investigated the use of BOV, presented in Coiffi et al [5]. The authors performed a thermodynamic and aerodynamic analysis of a BOV, showing a 29% reduction of MEL.…”
Section: Introductionmentioning
confidence: 99%